2016
DOI: 10.1186/s40880-016-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vascularization in murine models of primary and metastatic tumor growth

Abstract: Directed capillary ingrowth has long been considered synonymous with tumor vascularization. However, the vasculature of primary tumors and metastases is not necessarily formed by endothelial cell sprouting; instead, malignant tumors can acquire blood vessels via alternative vascularization mechanisms, such as intussusceptive microvascular growth, vessel co-option, and glomeruloid angiogenesis. Importantly, in response to anti-angiogenic therapies, malignant tumors can switch from one vascularization mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Previous studies of MVD as a potential predictive marker have given conflicting results [17,18,48]. A recent review on anti-angiogenic therapies by Bugyik et al proposes that the focus should be on patients where primary tumours have endothelial proliferation [49]. We found that proliferating vessels, expressed as VPI, have a stronger impact on prognosis than vessel density itself, and we propose that further studies on the predictive impact of VPI are needed.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies of MVD as a potential predictive marker have given conflicting results [17,18,48]. A recent review on anti-angiogenic therapies by Bugyik et al proposes that the focus should be on patients where primary tumours have endothelial proliferation [49]. We found that proliferating vessels, expressed as VPI, have a stronger impact on prognosis than vessel density itself, and we propose that further studies on the predictive impact of VPI are needed.…”
Section: Discussionmentioning
confidence: 68%
“…). Thus, the phenomena of vein wall vascularization with sprout formation from the intimal ECs, the polarized mode of migration (Bugyik et al, ), frequent mitoses, and initial microvessel expansion support a sprouting mechanism (Ausprunk and Folkman, ; Folkman and Shing, ; Díaz‐Flores et al, ; Ribatti and Crivellato, ). The participation of this type of angiogenesis is reinforced by the presence of mitoses in periendothelial cells of the growing vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on active metabolism of tumor cells on continuous desire to oxygen and nutrient, they release and produce high amounts of proangiogenic factors that promote nourishing the vessel growth . These are some main positive regulator of angiogenesis, such as vascular endothelial growth factor (VEGF), fibroblast growth factor‐2 (FGF‐2), interleukin‐8 (IL‐8), placental growth factor (PlGF), transforming growth factor beta (TGFbeta), platelet derived growth factor (PDGF), angiopoietins (Angs), etc …”
Section: Introductionmentioning
confidence: 99%